Integrated Marketing Communication PT. Bank Mandiri Taspen Capem Renon Dalam Peningkatan Loyalitas Nasabah - Awik Wirayani Purnama Dewi; I Dewa Ayu Hendrawathy Putri; I Wayan Wirta, Dr.Drs. I Wayan Wirta, M.Si (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2023)
ABSTRACT PT. Bank Mandiri Taspen Capem Renon is a banking industry which is a subsidiary of Bank Mandiri, which wants to get customers who are always loyal in using its products and services. PT. Bank Mandiri Taspen Capem Renon was previously less well knows by the public and other institutions, due to the lack of promotional updates, especially from social media. Therefore, PT. Bank Mandiri Taspen Capem Renon needs to apply the concept of integrated marketing communication (IMC), to understand the concept, reseaechers draw three problem formulations, namely: (1) IMC implementation in improving image, (2) communication barriers in the IMC implementation process, and (3) implications obtained in the IMC implementation process.Based on this formulation, the theories used to dissect the problem formulation are: (1) Promotion Mix Theory, (2) Communication Barriers Theory, and 93) SOR Theory. This research look place at PT. Bank Mandiri Taspen Capem Renon. The type of research used is qualitative, with the determination of informants using purposive sampling method. Data collection uses observation methods, interviews with guidelines assisted by voice recorder research tools and cellphones, literature and documentation. Data analysis conducted in this study uses data reduction, data presentation, and data verification.The findings of this study are in the implementation of PT. Bank Mandiri Taspen Capem Renon using the IMC concept by using promotional elements, namely advertising using print media and social media, personal selling by using a ball pick-up system to customer, sales promotion giving rewards to loyal customers, public relations by implementing workshops or seminars and also community service. During the implementation process, of course, there are obstacles, namely communication process barriers, physical barriers, frame of mind barriers, and technical barriers. During the marketing process with the IMC concept, of course, there will be implications that have an impact on all employees and also PT. Bank Mandiri Taspen, namely internal implications that have an impact on the community regarding the existence of PT. Bank Mandiri Taspen, marketing communication implications that have an impact on the promotional media carried out, as well as the implications of the IMC concept.Keywords: Integrated Marketing Communication, PT. Bank Mandiri Taspen, Customer Loyality